Pengaruh Penerapan E-Commerce terhadap Keputusan Pembelian pada skala UMKM - Ayu Falufi, Delfi; Chaniago, Harmon (International Journal Administration, Business & Organization, 2024)
This research aims to analyze the influence of implementing e-commerce on purchasing decisons on the MSME in Bandung, Indonesia. The research methodology used was descrptive quantitative, with primary data collected through distributing questionnaires to 108 respondents who implemented e-commerce. Data analysis involved descriptive, correlation and simple regression approaches. The findings of this research show that the application of e-commerce has a positive and significant effect on purchasing decisions on the SMEs scale.